2020
DOI: 10.1055/a-1265-3315
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in appropriateness and diagnostic yield of fast-track endoscopy during the COVID-19 pandemic in Northern Italy

Abstract: Background and study aim: During the COVID-19 outbreak in Italy only fast-track endoscopic procedures have been performed; nevertheless, a significant drop in their number has been reported. We evaluated whether the pandemic has impacted the appropriateness and diagnostic yield of fast-track endoscopic procedures in comparison with those performed in 2019. Patients and methods: This retrospective survey has involved Endoscopic Services in Northern Italy; we compared data regarding endoscopic procedures perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 16 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…During the COVID-19 epidemic, the number of screenings for gastric cancer has been decreased [ 2 , 4 , 5 , 15 19 , 27 ]. In Italy, the number of endoscopies has decreased by 53.6% compared to 2019 [ 19 ]. In the Netherlands, the rate of gastroscopy has decreased by 57%.…”
Section: Resultsmentioning
confidence: 99%
“…During the COVID-19 epidemic, the number of screenings for gastric cancer has been decreased [ 2 , 4 , 5 , 15 19 , 27 ]. In Italy, the number of endoscopies has decreased by 53.6% compared to 2019 [ 19 ]. In the Netherlands, the rate of gastroscopy has decreased by 57%.…”
Section: Resultsmentioning
confidence: 99%
“…The study from Northern Italy found a 44 % decline in the absolute number of new cancer diagnoses and a relatively small increase in the proportion of endoscopies with a cancer diagnosis (from 6.0 % to 7.3 %) [2]. Although this is a far smaller study ( < 3000 procedures), data were obtained from individual chart review and cancers were histologically confirmed.…”
mentioning
confidence: 76%
“…To that end, the study from Northern Italy made appropriateness of endoscopic procedures the main objective of the study [2]. Aside from a relative increase in cancer diagnoses, the study also found a dramatic increase in clinically relevant findings per endoscopic procedure.…”
mentioning
confidence: 97%
See 2 more Smart Citations